METHOD OF DISTRIBUTION OF TRAFFIC FLOW BASED ON THE TRANSPORT PROBLEM - Djurayev Sherzod Sobirjonovich; Madaliyev Xushnid Baxromjon o`g`li (Scholars Digest Publishing, 2023)
Connected and Intelligent Transportation Systems (C-ITS) are revolutionizing the way we manage and operate transport systems. However, with the increasing integration of digital technologies into transportation infrastructure, security becomes paramount. This article explores the development and application of mathematical models to enhance the security of C-ITS within the transport system. We discuss the key challenges, solutions, and implications of securing C-ITS and propose a roadmap for future research in this domain.
Keywords: Intelligent Transportation Systems, transport systems, transportation infrastructure, security, security of C-ITS, Quantum Key Distribution.